Analisa Pengetahuan Pecalang sebagai Pengatur Lalu Lintas - I Made Kariyana (Syntax Corporation Indonesia, 2024)
As a traditional security officer in Balinese society, Pecalang has a very important role, especially in keeping traditional and religious activities running. Along with the progress of the times, apart from being a security officer for traditional activities, Pecalang also has a duty as police intelligence in providing information about the areas it guards. The existence of this transformation of pecalang tasks requires pecalang to be more active in updating information and knowledge about the tasks that are being or will be carried out. In this study, the knowledge of pecalang was extracted on the task of pecalang as a traffic controller, both in carrying out the duties as the person in charge of diverting traffic flow and conditioning parking vehicles. The method used in this study is a method of collecting data with a questionnaire or questionnaire in which the questions asked are divided into several topics related to the task of pecalang as traffic controllers. Based on the analysis of the collected questionnaires, it was found that the knowledge of Pecalang in Pakraman Cemagi Village related to their duties as traffic controllers as follows: Pecalang already understands or knows about traffic and the duties of Pecalang, about traffic signs, about traffic procedures, and about parking. However, pecalangs do not understand or know less about traffic laws and regulations, about road markings and intersections, as well as about diversion, closure and classification of road divisions.